Effect of IMCI and Severe Acute Malnutrition Training on Health Workers’ Knowledge in East Kalimantan - Rudy Agus Riyanto; Ratih Wirapuspita Wisnuwardani; Iriyani Kamaruddin (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Stunting is a disorder of children's growth and development caused by chronic malnutrition and recurrent infections during the First 1000 Days of Life (HPK). Health workers at health centers, as part of the nutrition team, play a significant role in implementing effective interventions to reduce stunting rates. One of the trainings provided to health workers is the Integrated Management of Childhood Illness (IMCI) and Severe Acute Malnutrition training. This study aimed to measure changes in the knowledge of health workers before and after receiving the IMCI and Severe Acute Malnutrition training.This pre-experimental study involved 84 health workers from three cities in East Kalimantan. The training utilized interactive lectures, role play,  assignments, and practice sessions. A paired t-test was used to analyze the data. A significant increase in knowledge was observed before and after the training (p-value = 0.0001). It was concluded that the IMCI and Severe Acute Malnutrition Training was effective in enhancing the knowledge of health workers. Therefore, it remains essential as a routine training effort to prevent stunting.